Analysis of 19 Highly Conserved Vibrio cholerae Bacteriophages Isolated from Environmental and Patient Sources Over a Twelve-Year Period - Angus Angermeyer; Moon Moon Das; Durg Vijai Singh; Kimberley D. Seed (Viruses, 2018)
The Vibrio cholerae biotype “El Tor” is responsible for all of the current epidemic and endemic cholera outbreaks worldwide. These outbreaks are clonal, and it is hypothesized that they originate from the coastal areas near the Bay of Bengal, where the lytic bacteriophage ICP1 (International Centre for Diarrhoeal Disease Research, Bangladesh cholera phage 1) specifically preys upon these pathogenic outbreak strains. ICP1 has also been the dominant bacteriophage found in cholera patient stools since 2001. However, little is known about the genomic differences between the ICP1 strains that have been collected over time. Here, we elucidate the pan-genome and the phylogeny of the ICP1 strains by aligning, annotating, and analyzing the genomes of 19 distinct isolates that were collected between 2001 and 2012. Our results reveal that the ICP1 isolates are highly conserved and possess a large core-genome as well as a smaller, somewhat flexible accessory-genome. Despite its overall conservation, ICP1 strains have managed to acquire a number of unknown genes, as well as a CRISPR-Cas system which is known to be critical for its ongoing struggle for co-evolutionary dominance over its host. This study describes a foundation on which to construct future molecular and bioinformatic studies of these V. cholerae-associated bacteriophages.